Staff outdoor positioning in large area campus using GPS enabled phone, Google Map and mobile network - Leow, Daniel Vee Leon; Lau, Alan Kah Foo *; Grange, Terence Le; Laxman, Lyon *; Dharmidran Anantharsekaran, * (2011)
This paper explore the feasibility of using GPS enabled phone to locate staff in a large campus area on a customized campus map. This system provides an alternative approach to locate staff compared to static directory. GPS foot printing enable the system to determine which campus building that the staff is in. The map can be viewed on Internet connected browser via personal computer or mobile device.